Návrh úsporných opatření v oblasti elektrické energie pro firmy v České republice - Lomjanský, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalárska práca sa zaoberá návrhom úsporných opatrení v oblasti elektrickej energie pre firmy v Českej republike. Najskôr definuje niekoľko základných pojmov týkajúcich sa danej problematiky akými sú burza, hodinový diagram spotreby, apod. Neskôr popisuje trh s elektrickou energiou, definuje situáciu v Českej republike a zaoberá sa vznikom, vývojom a aktuálnou situáciou na burze PXE. Hlavných zámerom je predložiť konkrétne návrhy úsporných opatrení pri nákupe tejto komodity pre firmy v Českej republike a definovať ich použitie v praxi.

Bachelor thesis deals with the proposal of economical measures in the field of electric energy for companies in the Czech Republic. First, it defines basic terminology regarding the topic, e.g. stock exchange, hourly off-take diagram, etc. Then it describes electric energy market, it defines the situation in the Czech Republic and it focuses on formation, development and current situation on the PXE energy exchange. The main objective is to provide concrete suggestions of economical measures while buying this commodity for the companies in the Czech Republic and to define their practical use.
Proposal of Economical Measures in the Field of Electric Energy for Companies in the Czech Republic
Keywords: Elektrická energia; PXE; burza; náklady; hodinový diagram spotreby; Electric energy; stock exchange; expenses/costs; hourly off-take diagram